Cu5Ca-based powder and its manufacturing method

By preparing composite particles with the nanopore structure surface layer with the core of Ca inter-based metal compound and Cu as the main component, as the reduction catalyst of CO2, the problems of low selectivity and low energy efficiency of Cu catalysts in the prior art are solved, and efficient reduction of CO2 and effective formation of multi-carbon products are achieved.

JP7666259B2Active Publication Date: 2025-04-22KK TOYOTA CHUO KENKYUSHO
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021151544
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-09-16
Publication Date
2025-04-22
Estimated Expiration
2041-09-16

AI Technical Summary

Technical Problem

The prior art has problems of low selectivity and low energy efficiency when using Cu as a reduction catalyst, especially when preparing multi-carbon products such as ethylene.

Method used

Compound particles with a nanopore structure surface layer with a core of the Ca inter-based metal compound and Cu as the main component are prepared as a reduction catalyst for CO2. The method includes using Cu, CaCl2 and Na as raw materials, heating in an oxygen-free atmosphere to form Ca particles, and removing surface Ca by solvent cleaning or electric field application, to form a nanopore structure.

Benefits of technology

The efficient reduction of CO2 is achieved, the selectivity and energy efficiency of the catalyst are improved, and the reaction intermediate is activated through the nanopore structure, which promotes the formation of multi-carbon products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666259000008
    Figure 0007666259000008
  • Figure 0007666259000009
    Figure 0007666259000009
  • Figure 0007666259000010
    Figure 0007666259000010
Patent Text Reader

Abstract

To provide a novel Cu5Ca-based powder having a Cu5Ca intermetallic compound as a main component, and a method of producing the same.SOLUTION: A Cu5Ca-based powder includes a composite particle comprising a core, and a surface layer formed over a surface of the core, in which the core consists of a Cu5Ca intermetallic compound and the surface layer consists of a Cu5Ca1-xOy compound (0<x≤1, 0<y≤2.5) and has a nano-porous structure. Such a Cu5Ca-based powder is obtainable by preparing a raw material containing Cu, CaCl2 and Na, heating the raw material under an inert gas atmosphere into a reaction product containing a Cu5Ca particle, and drawing Ca out of at least a surface layer portion of the Cu5Ca particle.SELECTED DRAWING: Figure 13
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is 5 More specifically, the Ca-based powder and its manufacturing method are 5 Ca intermetallic compounds, CO 2 Cu is useful as a reduction catalyst 5 The present invention relates to a Ca-based powder and a method for producing the same. [Background technology]

[0002] "CO 2 The "reduction catalyst" is a type of carbon dioxide (CO 2 ) into useful substances. 2 Useful substances obtained by reduction include carbon monoxide (CO), syngas (CO + H 2 ), methane (CH 4 ), ethylene (C 2 H 4 ), ethane (C 2 H 6 ), ethanol (C 2 H 5 OH), propanol (C 3 H 7 OH) etc.

[0003] CO 2 Using a reduction catalyst, CO released into the atmosphere 2 The captured CO 2 It is possible to convert CO into useful substances and reuse them as resources. 2 The reduction reaction is CO 2 Emission reduction and CO 2 Therefore, CO 2 The search for catalysts that show high catalytic activity (high selectivity and high conversion efficiency) for the reduction reaction has been actively pursued. 2 The synthesis of multicarbon products such as ethylene using reduced catalysts generally suffers from low selectivity and low energy efficiency.

[0004] In order to solve this problem, various proposals have been made in the past. For example, Non-Patent Document 1 describes the application of KHCO containing KI to an electrolytically polished polycrystalline Cu electrode. 3 A method for reconstructing the Cu electrode surface by subjecting it to electrochemical oxidation-reduction cycling in an aqueous solution is disclosed. The same document states: (A) This method allows the production of a Cu film (Re-Cu-I) that is composed of entangled Cu nanowires and has a hierarchical porous structure; and (B) Re-Cu-I at -1.09 V vs. C at RHE 2 Faraday efficiency reaches 80% is stated.

[0005] A porous structure mainly composed of Cu can be obtained by using the method described in Non-Patent Document 1. In the example described in the same document, the porous structure is produced by electrochemically extracting oxygen from Cu oxide. On the other hand, an intermetallic compound is a compound containing two or more metal elements, and it is believed that a porous structure can be formed on the surface of the intermetallic compound by dissolving some of the constituent elements from the intermetallic compound. However, when a powder containing a Cu-containing intermetallic compound as the main component, a powder containing composite particles in which a porous structure is formed on the surface of a core made of a Cu-containing intermetallic compound, or a CO powder containing such a powder is used, 2 There have been no examples of reduction catalysts proposed in the past. [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Jianyu Han et al., Chem Sci., 2020, 11, 10698-10704 Summary of the Invention [Problem to be solved by the invention]

[0007] The problem to be solved by the present invention is Cu 5 to provide a novel Cu 5 Ca-based powder mainly composed of a Ca metal intermetallic compound. Another problem to be solved by the present invention is CO 2 to provide a novel Cu 5 Ca-based powder useful as a CO reduction catalyst. Furthermore, another problem to be solved by the present invention is to provide a novel method for producing such a Cu 5 Ca-based powder.

Means for Solving the Problems

[0008] The Cu 5 Ca-based powder according to the present invention for solving the above problems is composed of a core and a surface layer formed on the surface of the core, and includes composite particles, the core is composed of a Cu 5 Ca metal intermetallic compound, the surface layer is composed of a Cu 5 Ca 1-x O y compound (0 < x ≦ 1, 0 < y ≦ 2.5) and has a nanoporous structure. This is the gist.

[0009] The method for producing the Cu 5 Ca-based powder according to the present invention is a first step of preparing a raw material containing Cu, CaCl 2 , and Na, a second step of heating the raw material in an inert gas atmosphere to obtain a reaction product containing Cu 5 Ca particles, a third step of extracting Ca from at least the surface layer portion of the Cu 5 Ca particles to obtain the Cu 5 Ca-based powder according to the present invention, and is provided with.

Effects of the Invention

[0010] Cu, CaCl 2 When raw materials containing Na are heated, CaCl 2 is reduced by Na to produce Ca and NaCl. The Ca produced further reacts with Cu to produce Cu 5 Ca particles are generated. Since Cu has low solubility in molten Na, Cu particles generated in the presence of molten Na 5 The Ca particles do not grow large and become fine particles. In addition, by optimizing the raw material mixing ratio and heating conditions, 5 A reaction product containing Ca particles and containing little unreacted Cu is obtained.

[0011] Next, after removing unreacted Na from the obtained reaction product as necessary, the reaction product is washed with a solvent containing water and / or an electric field is applied to the reaction product in an electrolyte, whereby the water-soluble components contained in the reaction product are removed and at the same time, Cu is formed. 5 All or part of the Ca is removed from the surface of the Ca particle, resulting in a core of Cu. 5 Cu, which is made of Ca intermetallic compound, has a surface layer mainly composed of Cu, and contains composite particles having a nanoporous structure. 5 Ca-based powder is obtained.

[0012] The Cu obtained in this way 5 Ca-based powder is CO 2 It functions as a reduction catalyst. In addition, the surface layer with a nanoporous structure on the surface of the composite particles activates reaction intermediates and converts them into CO, such as ethylene. 2 It is considered that there is a possibility that the production of reduced products is promoted. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a flow diagram of the synthesis procedure for Cu5Ca-based powder and a schematic diagram of a reaction vessel used in the synthesis. [Diagram 2] 1 shows XRD patterns of the products obtained in Examples 1 and 2 and Comparative Example 2. [Diagram 3]1 is an XRD pattern of the product obtained in Example 3. [Figure 4] 1 is an SEM image of the product obtained in Comparative Example 2. [Diagram 5] 1 is an SEM image of the product obtained in Example 1.

[0014] [Figure 6] 1 is an SEM image of the product obtained in Example 2. [Figure 7] 1 is an SEM image of the product obtained in Example 3. [Figure 8] 1 is a cross-sectional STEM image of the product obtained in Example 3. [Figure 9] 2 shows the change in current density over time when evaluating the catalytic activity of the product obtained in Example 1.

[0015] [Figure 10] 1 shows the current efficiency (bar graph) at each applied voltage of the product obtained in Example 1. [Figure 11] 1 shows the change in current density over time when evaluating the catalytic activity of the product obtained in Example 3. [Figure 12] 1 shows the current efficiency (bar graph) at each applied voltage of the product obtained in Example 3. [Figure 13] 1 shows the current efficiency (line graph) at each applied voltage of the product obtained in Example 3. [Figure 14] 1 shows the current efficiency (bar graph) at each applied voltage of the product obtained in Comparative Example 1.

[0016] [Figure 15] 1 is an XRD pattern of the product obtained in Example 4. [Figure 16] 1 is an XRD pattern of the product obtained in Example 5. [Figure 17] Figure 17(A) is a cross-sectional STEM image of the product obtained in Example 5. Figure 17(B) is an enlarged cross-sectional STEM image of part (1) in Figure 17(A). Figure 17(C) is an enlarged cross-sectional STEM image of part (2) in Figure 17(A).

Best Mode for Carrying Out the Invention

[0017] Hereinafter, an embodiment of the present invention will be described in detail. [1. Cu 5 Ca-based powder] The Cu 5 Ca-based powder according to the present invention comprises composite particles including a core and a surface layer formed on the surface of the core. The core is composed of a Cu 5 Ca intermetallic compound. Furthermore, the surface layer is composed of a Cu 5 Ca 1-x O y compound (0 < x ≤ 1, 0 < y ≤ 2.5) and has a nanoporous structure.

[0018] [1.1. Microstructure] As described below, the Cu 5 Ca-based powder according to the present invention (a) is obtained by reacting a raw material containing Cu, CaCl 2 , and Na, or a raw material further containing NaCl in addition to these, (b) and extracting Ca from the surface layer of the Cu 5 Ca particles contained in the reaction product. In the Cu-Ca binary system, there are three types of intermetallic compounds: Cu 5 Ca, CuCa, and Ca 2 Cu. When the above-described method is used, a powder containing a Cu 5 Ca intermetallic compound as a main component can be obtained.

[0019] Specifically, when a raw material containing Cu, CaCl 2 , and Na is heated, CaCl 2 is reduced by Na (melting point: 98°C), and Ca and NaCl are generated. The generated Ca further reacts with Cu to generate Cu 5 Ca particles. When NaCl is further contained in the raw material, CaCl 2Since Ca and NaCl form a eutectic, the melting point of the raw material decreases, making it easier to generate a melt. When the melt is generated, the reaction between Ca and Cu is further promoted.

[0020] In the reaction product immediately after the reaction, Cu 5 Ca particles are contained. After removing unreacted Na from this reaction product as necessary, when the reaction product is washed with a solvent containing water and / or an electric field is applied to the reaction product in an electrolyte, the water-soluble components contained in the reaction product are removed, and at the same time, all or part of Ca elutes from the surface of the Cu 5 Ca particles. As a result, composite particles having a core and a surface layer formed on the surface of the core are generated.

[0021] In this case, the core consists of a Cu 5 Ca intermetallic compound. In the core, it is considered that the Cu / Ca ratio maintains 5 (integer ratio). On the other hand, the surface layer consists of Cu 5 Ca 1-x O y compound (0 < x ≤ 1, 0 < y ≤ 2.5). Since the surface layer is formed by eluting all or part of Ca from Cu 5 Ca existing near the surface of the particle, the Cu / Ca ratio exceeds 5. Also, since the oxygen concentration in the composite particles may increase after solvent washing, it is considered that the particle surface may be partially oxidized when Ca is eluted. Furthermore, since the surface layer is formed by eluting all or part of Ca from Cu 5 Ca, it has a nanoporous structure mainly composed of Cu.

[0022] The thickness of the surface layer varies depending on the Ca extraction method, extraction conditions, etc. For example, when the washing method described later is used as the Ca extraction method, the thickness of the surface layer is about 20 nm to 100 nm. On the other hand, when the electric field application method described later is used as the Ca extraction method, the thickness of the surface layer is about 500 nm to 2 μm. In any case, Cu at the location where Ca is extracted may be liberated and re-precipitated to form another pure Cu particle.

[0023] [1.2. Heterogeneity] The reaction products include Cu 5 In addition to Ca particles, unreacted raw materials (e.g., Cu, etc.) and by-products (e.g., Cu 2 O, calcium carbonate, etc.) may be included. Of these, Cu is insoluble or poorly soluble in the solvent. Therefore, if a relatively excessive amount of Cu is added to the raw materials, or if the raw materials are reacted under conditions that do not allow the reaction between the raw materials to proceed sufficiently, Cu may remain even after washing with the solvent. The amount of Cu remaining as an impurity was measured by XRD. 5 Intensity of the main peak of Ca I 0 The ratio of the intensity I of the main peak of Cu to the intensity I of the main peak of Cu (= I / I 0 ) can be expressed as When the method described later is used, optimizing the manufacturing conditions results in I / I 0 Cu with a ratio of 1.2 or less 5 Ca-based powder is obtained. By further optimizing the manufacturing conditions, I / I 0 Cu with a ratio of 1.0 or less, 0.50 or less, 0.20 or less, or less than 0.05 5 Ca-based powder is obtained.

[0024] [1.3. Average particle size] When the raw material is heated to a certain temperature, a Na melt is generated. Since Cu has low solubility in Na melt, the generated Cu melts in the presence of Na melt. 5 The Ca particles do not grow large and become fine particles. When the above-mentioned method is used, by optimizing the manufacturing conditions, it is possible to obtain Cu with an average primary particle size of 20 μm or less. 5 Ca-based powder can be obtained. By further optimizing the manufacturing conditions, the average particle size of the primary particles can be reduced to 5 μm or less. Here, the "average particle size of primary particles" refers to the average value of the longitudinal size of 20 or more primary particles (areas surrounded by grain boundaries) randomly selected under microscope observation.

[0025] [1.4. Usage] Cu according to the present invention 5 The Ca-based powder contains composite particles having a core and a surface layer formed on the surface of the core. The surface layer has a nanoporous structure mainly composed of Cu. Therefore, the Cu 5 Ca-based powder is CO 2 It is suitable as a reduction catalyst. Cu according to the present invention 5 Ca-based powder CO 2 When used as a reduction catalyst, the Cu-based nanoporous structure activates reactive intermediates, such as ethylene, to produce CO 2 It is considered that there is a possibility that the production of reduced products is promoted.

[0026] [2. Cu 5 Manufacturing method of Ca-based powder] Cu according to the present invention 5 The manufacturing method of Ca-based powder is as follows: Cu, CaCl 2 A first step of preparing a raw material containing Na; The raw material is heated under an inert gas atmosphere to form Cu 5 A second step of obtaining a reaction product containing Ca particles; Cu 5 The Ca is extracted from at least the surface layer of the Ca particles, and the Cu 5 The third step is to obtain Ca-based powder. It is equipped with: Cu according to the present invention 5 The method for producing a Ca-based powder may further include a fourth step, after the second step and before the third step, of removing unreacted Na from the reaction product.

[0027] [2.1. 1st step] First, Cu, CaCl 2 A raw material containing Na and Zn is prepared (first step). The raw material may further contain NaCl. Of these, Cu and CaCl 2 Cu 5 It is the main raw material for synthesizing Ca. Na is CaCl 2It is a reducing agent that reduces Ca to produce Ca. NaCl is CaCl 2 It forms a eutectic with NaCl, which has the effect of lowering the melting point of the raw material. Although NaCl is not always necessary, adding NaCl to the raw material makes it easier for more melt to be produced during the reaction. As a result, the reaction may proceed at a lower temperature.

[0028] The blending ratio of the raw materials is not particularly limited, and an optimal blending ratio can be selected depending on the purpose. In general, the raw material Cu / CaCl 2 If the molar ratio becomes too small, unreacted CaCl 2 Therefore, Cu / CaCl 2 The ratio is preferably 1.0 or more. Cu / CaCl 2 More preferably, the ratio is 3.0 or greater. On the other hand, Cu / CaCl 2 If the ratio is too high, a large amount of unreacted Cu may remain. 2 The ratio is preferably 5.0 or less.

[0029] Na is CaCl 2 The reducing agent is CaCl 2 To reduce all of the 2 Therefore, the Na / CaCl ratio in the raw material is twice as large as the number of moles of Na. 2 If the molar ratio becomes too small, unreacted CaCl 2 Therefore, Na / CaCl may remain in large amounts. 2 The ratio is preferably 2.0 or more. 2 More preferably, the ratio is 4.0 or greater. On the other hand, Na / CaCl 2 If the ratio is too large, a large amount of unreacted Na may remain. 2 The ratio is preferably 5.0 or less.

[0030] NaCl and CaCl 2The melting points of each of these compounds alone are around 800°C. 2 A composition with a molar ratio of 1:1 is a eutectic composition, and the melting point drops to about 500°C. Therefore, when NaCl is contained in the raw material, the NaCl / CaCl ratio in the raw material 2 If the molar ratio becomes too small, the melting point of the raw material will increase. 2 The ratio is preferably 0.5 or more. 2 More preferably, the ratio is 1.0 or greater. Similarly, NaCl / CaCl 2 If the ratio becomes too large, the melting point of the material will increase. 2 The ratio is preferably less than or equal to 2.0.

[0031] [2.2. 2nd process] Next, the raw material is heated under an inert gas atmosphere to form Cu 5 A reaction product containing Ca particles is obtained (second step). The heating temperature of the raw material is preferably selected to be optimal depending on the raw material composition. In general, if the heating temperature is too low, the reaction may not proceed sufficiently within a practical time. Therefore, the heating temperature is preferably 600°C or higher. On the other hand, if the heating temperature is too high, the intermetallic compound may decompose and return to Cu, so the heating temperature is preferably 900° C. or lower.

[0032] The heating time is not particularly limited as long as the reaction between the raw materials proceeds sufficiently, and it is preferable to select an optimal heating time depending on the heating temperature. Moreover, the heating is preferably carried out in an inert gas atmosphere in order to prevent oxidation of the raw materials.

[0033] [2.3. Third step] Next, the Cu 5 The Ca is extracted from at least the surface layer of the Ca particles (third step). 5 Ca-based powder is obtained. Cu 5The method for extracting Ca from the surface layer of the Ca particles is not particularly limited as long as it is possible to extract Ca. Examples of such methods include (a) A method of washing the reaction product with a solvent containing water (washing method), (b) A method in which an electric field is applied to the reaction product in an electrolyte (electric field application method) etc.

[0034] [2.3.1. Cleaning method] Cu 5 When the reaction product containing Ca particles was washed with a solvent containing water, Cu 5 It is possible to extract Ca from at least the surface layer of the Ca particles. In addition, the raw material and the reaction product contain Ca, CaCl 2 The reaction products contain water-soluble components such as Ca, NaCl, etc. If a solvent containing water is used as a washing solvent for the reaction products, these water-soluble components can be removed at the same time as Ca is extracted.

[0035] The solvent containing water is Cu 5 There is no particular limitation as long as it is capable of extracting Ca from the surface layer of the Ca particles. (a) water, (b) Alkaline aqueous solutions such as NaOH aqueous solutions, (c) Acidic aqueous solutions such as aqueous HCl solutions; (d) a mixed solvent of water and an organic solvent; etc. The washing conditions are not particularly limited as long as they allow extraction of Ca. Washing may be performed once using one type of solvent, or multiple times using multiple types of solvents with different compositions.

[0036] [2.3.2. Electric field application method] First, Cu 5 An electrode is made using the reaction product containing Ca particles. This electrode is immersed in an electrolyte and CO 2 When an electric field is applied to the electrodes while blowing in Cu 5It is possible to extract Ca from at least the surface layer of Ca particles. Because the electrolyte contains water, when the electrode is immersed in the electrolyte, the Ca is extracted and the water-soluble components are also removed. The electric field application method requires more complicated steps than the washing method, but has the advantage of being able to form a nanoporous structure deeper from the surface layer of the particles. The electric field application method may be used alone or in combination with the cleaning method. When the cleaning method and the electric field application method are combined, the electric field application method may be performed before the cleaning method or after the cleaning method.

[0037] The electrolyte is Cu 5 There is no particular limitation on the electrolyte, so long as it is possible to extract Ca from the surface layer of the Ca particles. Examples of the electrolyte include an aqueous solution of potassium hydrogen carbonate, an aqueous solution of hydrogen chloride, and an aqueous solution of sulfuric acid. The application of an electric field causes CO 2 It is preferable to blow in Cu. 5 CO on the surface of Ca particles 2 This is because a reaction occurs between Ca and protons, which consumes protons and increases the pH locally, making it easier for Ca to be released. The conditions for applying the electric field are not particularly limited, and the optimum conditions can be selected depending on the purpose. In general, the stronger the electric field applied to the electrodes and / or the longer the application time of the electric field, the more Ca can be extracted.

[0038] [2.4. 4th step] When a relatively large amount of Na is added to the raw material, unreacted Na may remain in the reaction product. In such a case, if the reaction product is washed directly with a solvent containing water or brought into contact with an electrolyte, Na may react violently with water and cause a fire. In such a case, it is preferable to remove unreacted Na from the reaction product before extracting Ca (fourth step).

[0039] The method for removing Na is not particularly limited as long as it can safely remove unreacted Na from the reaction product. The method for removing Na is preferably a method for washing the reaction product with alcohol. When the reaction product containing Na is washed with alcohol, Na reacts with the alcohol to generate sodium alkoxide that is soluble in alcohol. As a result, Na can be safely removed from the reaction product.

[0040] The washing conditions are not particularly limited, and the optimum conditions can be selected according to the purpose. In general, the reaction with Na proceeds more gently with a longer chain alcohol. Therefore, it is preferable to wash the reaction product several times using several kinds of alcohol so that the chain length is successively shorter. For example, it is preferable to wash the reaction product with propanol, then with ethanol, and further with methanol.

[0041] [3. Effect] Cu, CaCl 2 When raw materials containing Na are heated, CaCl 2 is reduced by Na to produce Ca and NaCl. The Ca produced further reacts with Cu to produce Cu 5 Ca particles are generated. Since Cu has low solubility in molten Na, Cu particles generated in the presence of molten Na 5 The Ca particles do not grow large and become fine particles. In addition, by optimizing the raw material mixing ratio and heating conditions, 5 A reaction product containing Ca particles and containing little unreacted Cu is obtained.

[0042] Next, after removing unreacted Na from the obtained reaction product as necessary, the reaction product is washed with a solvent containing water and / or an electric field is applied to the reaction product in an electrolyte, whereby the water-soluble components contained in the reaction product are removed and at the same time, Cu is formed. 5 All or part of the Ca is removed from the surface of the Ca particle, resulting in a core of Cu. 5 Cu, which is made of Ca intermetallic compound, has a surface layer mainly composed of Cu, and contains composite particles having a nanoporous structure.5 Ca-based powder is obtained.

[0043] The Cu obtained in this way 5 Ca-based powder is CO 2 It functions as a reduction catalyst. In addition, the surface layer with a nanoporous structure on the surface of the composite particles activates reaction intermediates and converts them into CO, such as ethylene. 2 It is considered that there is a possibility that the production of reduced products is promoted. EXAMPLES

[0044] (Examples 1 to 3, Comparative Examples 1 to 2) [1. Sample preparation] [1.1. Examples 1 to 3, Comparative Example 2] Figure 1 shows the Cu 5 The flow diagram of the synthesis procedure for Ca-based powder and a schematic diagram of the reaction vessel used for the synthesis are shown below. First, Cu, CaCl 2 , and NaCl were mixed to obtain a mixed powder. A predetermined amount of metallic Na was further added to this mixed powder to obtain a raw material mixture. The amounts of each raw material were adjusted so that the total amount of the mixed powder and metallic Na was about 200 mg.

[0045] The reaction vessel 10 includes a stainless steel cell 12, a BN crucible 14 inserted into the cell, and a lid 16 for sealing the opening of the cell 12. In an Ar atmosphere, a raw material mixture 20 was placed in the BN crucible 14, which was then inserted into the cell 12. Furthermore, the opening of the cell 12 was sealed with the lid 16. In this state, the reaction vessel 10 was heated to 400 to 750°C. After the reaction was completed, the reaction vessel 10 was cooled to room temperature, and the sample was taken out of the reaction vessel 10 in the air. The reaction product was then washed with propanol. It was then further washed with different solvents, in this order: ethanol, methanol, and water. The collected solid matter was then vacuum dried at 80°C for 2 hours.

[0046] [1.2. Comparative Example 1] Commercially available Cu powder was used for the test as is.

[0047] Table 1 shows the preparation conditions for each sample. [Table 1]

[0048] In the present invention, metallic Na and CaCl 2 The intention is to produce NaCl and Ca from the mixture and at the same time bring Ca and Cu into contact with each other through the melt and cause them to react. In addition, CaCl 2 Ca and NaCl each have a melting point of about 800°C when used alone. On the other hand, when the two are mixed and the mixture has a eutectic composition (molar ratio of about 1:1), the melting point drops to about 500°C. The reason NaCl is added to the system in advance is to generate a molten liquid at a lower temperature and promote the reaction between Ca and Cu.

[0049] 2. Test Method [2.1. X-ray diffraction (XRD) measurements] The reaction products were identified using XRD. [2.2. Electron microscope observation] The reaction products were observed and the average particle size of the primary particles was measured using a scanning electron microscope (SEM), and the cross sections of the reaction products were observed and their compositions were analyzed using a scanning transmission electron microscope (STEM).

[0050] [2.3. CO 2 Evaluation of reduction catalytic activity] The sample powder (approximately 4 mg) was rubbed onto the surface of carbon paper (CP) using a microspatula. This was placed in an electrolytic cell as the working electrode (WE). Platinum foil (Pt foil) was used as the counter electrode (CE), and an Ag / AgCl electrode was used as the reference electrode (RE). The WE and CE were separated using a cation exchange membrane. The electrolyte was 0.5 M potassium bicarbonate (KHCO 3 ) aqueous solution was used. CO 2While supplying gas (flow rate: 10 sccm) from the rear side (CP side) of the WE, a potential of -1.2 to -2.4 V was applied to the WE with the RE as the reference. The current flowing through the WE at this time was measured with a potentiostat. The concentration of the gas generated from the WE side was measured with a gas chromatograph.

[0051] Here, the current efficiency (%), which is an index of catalytic activity, was calculated as follows. We assumed that the concentration (ppm) of the components in the generated gas sampled at a certain point during the measurement was kept constant during the measurement time (t minutes), and calculated the amount of gas generated (mL) in t minutes using the following formula. Amount produced (mL) = product concentration (ppm) × flow rate (10sccm) × time (tmin)

[0052] Next, the number of moles of each gas was calculated from the amount (mL) of each gas produced and its molecular weight. The number of electrons required to produce each gas is H 2 2 in, 2 in CO, 2 in CH 4 8 pieces, C 2 H 4 12 pieces, C 2 H 6 16 in ethanol (EtOH), 12 in 1-propanol (PrOH), and 16 in 1-propanol (PrOH). The amount of electricity flowing in t minutes was calculated by integrating the measured current value over time. Using these values, the current efficiency was calculated using the following formula. Current efficiency (%) = (number of moles x number of electrons) / (amount of electricity / Faraday constant) x 100

[0053] [3. Results] [3.1. XRD measurement] Figure 2 shows the XRD patterns of the products obtained in Examples 1 and 2 and Comparative Example 2. Figure 3 shows the XRD pattern of the product obtained in Example 3. Furthermore, Table 2 shows the peak intensity ratios of the strongest XRD rays. The following can be seen from Figures 2, 3, and Table 2.

[0054] (1) Cu, Cu+Cu depending on the composition and heating temperature 5 Ca or Cu 5In Examples 1 to 3, powder of Cu was obtained. 5 Intensity of the main peak of Ca (I 0 The ratio of the intensity (I) of the main peak of the heterogeneous phase (Cu) to the intensity (I / I 0 ) was greater than 0 and less than 1.2.

[0055] (2) In this example, Cu and CaCl 2 is used as the metal source and Na is used as the reducing agent. When heated, CaCl 2 is reduced by Na (melting point: 98°C) to produce Ca and NaCl, and at the same time, the Ca reacts with Cu to produce Cu. 5 It is believed that Ca is produced.

[0056] Where CaCl 2 The melting points of Cu and NaCl alone are around 800°C, but when they are mixed together the melting point drops. In the case of a eutectic composition, the melting point is around 500°C. If there is no molten liquid in the system, a solid-phase reaction occurs, and the combination of Cu and Ca only progresses where Cu and Ca are in physical contact, leaving unreacted Cu behind. On the other hand, NaCl was added in advance, and CaCl 2 It is believed that the reaction proceeds at a lower temperature by preliminarily adding a mixed salt of Cu + NaCl. 5 It is believed that the ratio of Ca to Cu changes.

[0057] [Table 2]

[0058] [3.2. Electron microscope observation] [3.2.1. Average particle size of primary particles] [A. Comparative example 2] Fig. 4 shows an SEM image of the product obtained in Comparative Example 2. Table 3 shows the results of measuring the size of primary particles of the product obtained in Comparative Example 2. The particle numbers in Table 3 correspond to the numbers in Fig. 4. In Fig. 4, the part surrounded by the grain boundary was regarded as a primary particle. From Fig. 4 and Table 3, it was found that the longitudinal size of most particles was in the range of 0.7 to 3.8 µm.

[0059] [Table 3]

[0060] B. Example 1 FIG. 5 shows an SEM image of the product obtained in Example 1. Table 4 shows the results of measuring the size of primary particles of the product obtained in Example 1. The particle numbers in Table 4 correspond to the numbers in FIG. 5. In FIG. 5, the portion surrounded by the grain boundary was regarded as a primary particle. From FIG. 5 and Table 4, it was found that the longitudinal size of most particles was in the range of 0.7 to 9.0 μm.

[0061] [Table 4]

[0062] C. Example 2 FIG. 6 shows an SEM image of the product obtained in Example 2. Table 5 shows the results of measuring the size of primary particles of the product obtained in Example 2. The particle numbers in Table 5 correspond to the numbers in FIG. 6. In FIG. 6, the portion surrounded by the grain boundary was regarded as a primary particle. From FIG. 6 and Table 5, it was found that the longitudinal size of most particles was in the range of 4.0 to 19.3 μm.

[0063] [Table 5]

[0064] D. Example 3 FIG. 7 shows an SEM image of the product obtained in Example 3. Table 6 shows the results of measuring the size of primary particles of the product obtained in Example 3. The particle numbers in Table 6 correspond to the numbers in FIG. 7. In FIG. 7, the portion surrounded by the grain boundary was regarded as a primary particle. From FIG. 7 and Table 6, it was found that the longitudinal size of most particles was in the range of 3.5 to 8.6 μm.

[0065] [Table 6]

[0066] [3.2.2. Nanoporous structure] Figure 8 shows a cross-sectional STEM image of the product obtained in Example 3. Table 7 shows the results of EDS analysis of the surface layer (square region shown in Figure 8(A)), the interface between the surface layer and the inside of the bulk (square region shown in Figure 8(B)), and the inside of the bulk (square region shown in Figure 8(C)) of the product obtained in Example 3. The following can be seen from Figure 8 and Table 7. (1) The dark contrast seen in the surface layer (thickness: several tens of nm) is thought to be voids. The surface layer was rich in Cu relative to Ca. It is thought that the loss of Ca from the surface layer formed a nanoporous structure. (2) As a result of the component analysis, in addition to Cu, C and O were detected. These are thought to be components derived from the resin used to hold the powder. However, since the oxygen concentration in the surface layer increased, it is thought that part of the surface layer has been oxidized.

[0067] [Table 7]

[0068] [3.3. CO 2 Redox catalytic activity] 3.3.1. Example 1 Figure 9 shows the change over time in current density when evaluating the catalytic activity of the product obtained in Example 1. Figure 10 shows the current efficiency (bar graph) at each applied voltage of the product obtained in Example 1. The following can be seen from Figures 9 and 10. (1) In Example 1, ethylene (C 2 H 4 ), ethane (C 2 H 6 ), methane (CH 4 ) and other CO 2 The reduction product was identified. (2) When the applied voltage is changed, CO 2 It was found that the ratio of reduction products changed.

[0069] 3.3.2. Example 3 Fig. 11 shows the change over time in current density when evaluating the catalytic activity of the product obtained in Example 3. Fig. 12 shows the current efficiency (bar graph) at each applied voltage of the product obtained in Example 3. Furthermore, Fig. 13 shows the current efficiency (line graph) at each applied voltage of the product obtained in Example 3. The following can be seen from Figs. 11 to 13. (1) In Example 3, ethylene (C 2 H 4 ), ethane (C 2 H 6 ), methane (CH 4 ), ethanol (EtOH), propanol (PrOH), etc. 2 The reduction product was identified. (2) When the applied voltage is changed, CO 2 It was found that the ratio of reduction products changed.

[0070] [3.3.3. Comparative Example 1] Fig. 14 shows the current efficiency (bar graph) at each applied voltage of the product obtained in Comparative Example 1. The following can be seen from Fig. 14. (1) In Comparative Example 1 (Cu powder), ethylene (C 2 H 4 ), ethanol (EtOH), propanol (PrOH), etc. 2 A reduction product was obtained. However, in Comparative Example 1, CO2 The production efficiency of the reduction product was significantly lower than that of Example 1 or Example 3. (2) Comparative Example 1 is CO 2 Also, in the point that a larger negative potential had to be applied to generate the reduction product, the current efficiency was lower than in Examples 1 to 3. This is considered to be because the surface layer portion of the Cu powder did not have a nanoporous structure.

[0071] Example 4 [1. Sample preparation] In the same manner as in Example 3, Cu 5 Ca-based powder (powder in which Ca was extracted by washing with water) was prepared. Next, the obtained Cu 5 The Ca-based powder was immersed in a 0.5M NaOH aqueous solution for 2 hours, then washed with water and dried in vacuum.

[0072] [2. Test Method and Results] The reaction product was identified using XRD. FIG. 15 shows the XRD pattern of the product obtained in Example 4. From FIG. 15, it can be seen that the product obtained in Example 4 contains Cu. 5 The main component is Ca, with trace amounts of Cu, Cu 2 In the case of Example 4, it was found that the powder contained I / I 0 The ratio was 0.09.

[0073] Example 5 [1. Sample preparation] In the same manner as in Example 3, Cu 5 Ca-based powder (powder in which Ca was extracted by washing with water) was prepared. Next, the obtained powder (approximately 4 mg) was rubbed onto the surface of carbon paper (CP) using a microspatula. This was placed in an electrolytic cell as the working electrode (WE). Platinum foil (Pt foil) was used as the counter electrode (CE), and an Ag / AgCl electrode was used as the reference electrode (RE). The WE and CE were separated using a cation exchange membrane. The electrolyte was 0.5 M potassium bicarbonate (KHCO 3 ) aqueous solution was used. CO 2While supplying water (flow rate: 10 sccm) from the rear surface (CP side) of the WE, a potential of −2.0 V was applied to the WE for 8 hours with the RE as the reference.

[0074] [2. Test Method and Results] [2.1. XRD measurement] The reaction product was identified using XRD. FIG. 16 shows the XRD pattern of the product obtained in Example 5. From FIG. 16, the product obtained contains Cu. 5 The main component is Ca, with trace amounts of Cu, Cu 2 In the case of Example 5, it was found that the powder contained I / I 0 The ratio was 0.13.

[0075] [2.2. Electron microscope observation] The cross section of the reaction product was observed using STEM. Figure 17(A) shows a cross-sectional STEM image of the product obtained in Example 5. Figure 17(B) shows an enlarged cross-sectional STEM image of part (1) in Figure 17(A). Figure 17(C) shows an enlarged cross-sectional STEM image of part (2) in Figure 17(A). FIG. 17 shows that the composite particles obtained in Example 5 have a nanoporous structure extending from the surface layer of the particles to a deeper region compared to the composite particles contained in the powder (Example 3) immediately after washing with water.

[0076] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]

[0077] Cu according to the present invention 5 Ca-based powder is CO 2 It can be used as a reduction catalyst.

Claims

1. A core, a surface layer formed on the surface of the core; Composite particles comprising: The core is Cu 5 It is made of Ca intermetallic compound, The surface layer is Cu 5 Ca 1-x O y The compound (0<x≦1, 0<y≦2.5) has a nanoporous structure. Cu 5 Ca series powder.

2. In XRD, Cu 5 Intensity of the main peak of Ca I 0 The ratio of the intensity I of the main peak of Cu to the intensity I of the main peak of Cu (= I / I 0 2. The Cu alloy according to claim 1, wherein 5 Ca-based powder.

3. The I / I 0 The Cu according to claim 2, wherein 5 Ca-based powder.

4. The Cu alloy according to any one of claims 1 to 3, wherein the average particle size of the primary particles is 20 µm or less. 5 Ca-based powder.

5. CO 2 The Cu according to any one of claims 1 to 4, which is used as a reduction catalyst. 5 Ca-based powder.

6. Cu, CaCl 2 A first step of preparing a raw material containing Na; The raw material is heated under an inert gas atmosphere to form Cu 5 A second step of obtaining a reaction product containing Ca particles; The Cu 5 The Cu particles according to any one of claims 1 to 5 are extracted with Ca from at least the surface layer of the Ca particles. 5 A third step of obtaining Ca-based powder; Cu 5 A method for producing Ca-based powder.

7. The Cu according to claim 6, wherein the third step includes a step of washing the reaction product with a solvent containing water. 5 A method for producing Ca-based powder.

8. The third step is to immerse the electrode containing the reaction product in an electrolyte and 2 The Cu alloy according to claim 6 or 7, further comprising a step of applying an electric field to the electrodes while blowing in the Cu alloy. 5 A method for producing Ca-based powder.

9. The Cu alloy according to any one of claims 6 to 8, further comprising a fourth step of removing unreacted Na from the reaction product after the second step and before the third step. 5 A method for producing Ca-based powder.

10. The Cu alloy according to any one of claims 6 to 9, wherein the raw material further contains NaCl. 5 A method for producing Ca-based powder.

11. The raw material Cu / CaCl 2 The Cu alloy according to any one of claims 6 to 10, wherein the molar ratio is 1.0 or more and 5.0 or less. 5 A method for producing Ca-based powder.

Citation Information

Patent Citations

  • Method of preparing calcium-copper composite microsphere with porous hollow structure based on hydrothermal reaction

    CN109675516A

  • Method for preparing carbon-containing compound by electro-catalyzing carbon dioxide with copper alloy material

    CN111074294A

  • Preparation of catalyst

    JP1980067336A

  • Catalyst for water gas shift reaction

    JP2004321924A

  • Silicon material including copper, method for producing the same, anode active material, and secondary battery

    JP2015224164A